2019
DOI: 10.1103/physrevfluids.4.093905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isothermal stratification strength on vorticity dynamics for single-mode compressible Rayleigh-Taylor instability

Abstract: The effects of isothermal stratification strength on vorticity dynamics for single-mode Rayleigh-Taylor instability (RTI) are examined using two dimensional fully compressible wavelet-based direct numerical simulations. The simulations model low Atwood number (A = 0.04) RTI development for four different stratification strengths, corresponding to Mach numbers from 0.3 (weakly stratified) to 1.2 (strongly stratified), and for three different perturbation Reynolds numbers, from 5,000 to 20,000. All simulations u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…The generation mechanism of acoustic waves in two-fluid miscible RTI [44,45] is different. In the latter case, it is the enthalpy diffusion term in the energy equation leading to non-zero time derivative and the generation of acoustic waves,…”
Section: Initial Acoustic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation mechanism of acoustic waves in two-fluid miscible RTI [44,45] is different. In the latter case, it is the enthalpy diffusion term in the energy equation leading to non-zero time derivative and the generation of acoustic waves,…”
Section: Initial Acoustic Effectsmentioning
confidence: 99%
“…(3) Are there fundamental differences in RTI bubble growth between 2D and 3D? Previous studies of late-time bubble growth were either restricted to 2D [38,44,45] or included 3D but were numerically under-resolved [35,37]. The absence of vortex stretching in 2D RTI makes the underlying vortex dynamics significantly different from 3D RTI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wieland et al. (2019) found that the dilatation effects also have an important influence on the evolution of vorticity for the compressible RTI, such as total baroclinic effects. They also revealed that bubble and spike asymmetries in RTI growth were formed as a consequence of the dilatation and stratification contributions to the baroclinic torque based on the analysis of the vorticity transport equation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the very large accelerations in these experiments, one might question comparison with results from other incompressible experiments and simulations. To test the incompressible assumption, we calculated the static Mach number as defined by Wieland et al [36] and find it to exceed 0.3 only at the largest acceleration levels and only in the SF 6 gas where it achieves a value of 0.35. In addition, the static Mach number is generally well below 0.3.…”
Section: Image Analysismentioning
confidence: 99%